Self-tracking in the Digital Era: Biopower, Patriarchy, and the New Biometric Body Projects. (March 2017) - Sanders, Rachel
This article employs Foucauldian and feminist analytics to advance a critical approach to wearable digital health- and activity-tracking devices. Following Foucault's insight that the growth of individual capabilities coincides with the intensification of power relations, I argue that digital self-tracking devices (DSTDs) expand individuals' capacity for self-knowledge and self-care at the same time that they facilitate unprecedented levels of biometric surveillance, extend the regulatory mechanisms of both public health and fashion/beauty authorities, and enable increasingly rigorous body projects devoted to the attainment of normative femininity. These technologies of surveillance, normalization, and discipline thus function to augment, and facilitate the cooperation of, neoliberal-era biopower and post-feminist patriarchal power. My analysis of digital self-tracking devices' instrumentality to biopower and patriarchy contributes to the emergent field of critical digital health studies and builds new connections between political, social, and feminist theories of embodiment; biopower studies; fat studies; and trans-disciplinary body studies.